2019
DOI: 10.4239/wjd.v10.i11.517
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and urinary biomarkers of non-albuminuric and albuminuric chronic kidney disease in patients with type 2 diabetes

Abstract: BACKGROUNDA number of recent studies indicate a transformation in the natural course of chronic kidney disease (CKD) in type 2 diabetes (T2D) patients: an increasing prevalence of declined renal function without proceeding to the accompanying elevation of albuminuria. It has been suggested that albuminuric and non-albuminuric CKD patterns could be different in their phenotypes and pathogenic mechanisms.AIMTo identify the risk factors and biomarkers of albuminuric and non-albuminuric patterns of CKD in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
(70 reference statements)
2
12
0
Order By: Relevance
“…The findings of this study were consistent with those of previous reports, including the most recent report of the National Health Research Institutes Annual Report on Kidney Disease in the urine protein to creatinine ratio (UPCR) [ 4 ] and the red blood cell count (RBC) [ 5 ], and Xiao’s report on the prediction of chronic kidney disease in proteinuria (PRO) [ 35 ]. The findings of the albumin (ALB) and fasting glucose level (GLU) are consistent with previous studies following Korbut et al [ 36 ] and Kshirsagar et al [ 37 ]. Similarly, Xue et al [ 38 ], Mahmood et al [ 39 ], and Kshirsagar et al [ 37 ] reported that triglycerides (TG), age, and gender are critical for prediction of chronic kidney disease.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study were consistent with those of previous reports, including the most recent report of the National Health Research Institutes Annual Report on Kidney Disease in the urine protein to creatinine ratio (UPCR) [ 4 ] and the red blood cell count (RBC) [ 5 ], and Xiao’s report on the prediction of chronic kidney disease in proteinuria (PRO) [ 35 ]. The findings of the albumin (ALB) and fasting glucose level (GLU) are consistent with previous studies following Korbut et al [ 36 ] and Kshirsagar et al [ 37 ]. Similarly, Xue et al [ 38 ], Mahmood et al [ 39 ], and Kshirsagar et al [ 37 ] reported that triglycerides (TG), age, and gender are critical for prediction of chronic kidney disease.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies revealed that gender is associated with CKD deterioration [3,22,23]. The urine protein (PRO)-to-urine creatinine ratio (UPCR) is the most important risk factor this consequence [24][25][26]. The UPCR is used for the next section of analyzing the impact of gender differences to predict the risk factors for CKD.…”
Section: Procedures and Data Analysismentioning
confidence: 99%
“…Mutation-caused abnormalities of the nephrin gene result in congenital nephrotic syndrome of the Finnish type[ 18 ]. The increased urinary excretion of nephrin is associated with the albuminuric pattern of CKD in patients with T2D[ 19 ]. Since the slit diaphragm provides the most selective barrier for albumin[ 20 ], it can be assumed that the anti-albuminuric action of SGLT2 inhibitors could be mediated by an effect on podocytes.…”
Section: Introductionmentioning
confidence: 99%